The Double-sided Synchronous TIG Procedure and Matching Analysis of Corresponding Joint of X7Ni9 Steel. (2015) - Huang, J.X.
Abstract: X7Ni9 steel plates (13 mm thickness) were welded using two processes with corresponding consumables, the filler metals are ERNiCrMo-4 wire and ENiCrFe-9 electrode respectively for the tungsten inert gas arc welding (TIG) and shield metal arc welding (SMAW). After backing weld of double-sided synchronous TIG, the regular TIG and SMAW will be carried out respectively to process the filling welding. The microstructures and mechanical properties of two kinds of joints are analyzed, the result shows that the impact energy at -196 ̊C in different zones of two joints reach to 70J and more, the lower heat input of TIG is more favorable for improving the impact toughness of joints. And the weld metal strength is lower than that of the base metal, but the transverse tensile strength all exceeds the lowest limit of the base metal, it indicated that the weld joint can achieve equal strength matching. Furthermore, the double-sided synchronous TIG could reduce the work of overhead welding for X7Ni9, the welding appearance and the welding quality could be improved.